South Asia Economic Focus, Spring 2014 : Time to Refocus - World Bank (Washington, DC, 2014)
South Asia experienced a strong cyclical rebound in 2013Q3 growth but has since slowed again. The strong regional growth performance between July and September 2013 can be largely attributed to a temporary pick up in export growth, investment activity, as well as stronger agricultural output. Since the large impact of global portfolio rebalancing in May 2103, emerging markets have separated into a diverse group ranging from continuously fragile to resilient vis-a-vis external pressures. India has managed to turn around the wheel and minimize exposure to further tapering in 2014. Weak growth and exchange rate depreciation have characterized India for some time. Capital inflows into South Asia have regained some momentum and proved more resilient in January 2014 as opposed to May 2013. This report presents recent economic developments; outlook and policy; focus: from external to domestic risk; South Asia country briefs for Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka; and South Asia at a glance.